Ethnolinguistic Vitality, Identity and Power: Investment in SLA. (January 2021) - Clément, Richard; Norton, Bonny
This article concerns the relationship between social context, identity and intergroup relations. It reviews early formulations pertaining to contextual influences and proceeds to examine vitality theory, specifically, ethnolinguistic vitality (EV). The ensuing discussion considers objective aspects of EV such as the demographic representation of a group and delineates multiple influences modulating their impact on intergroup relations. Subjective formulations of EV focusing on how it is perceived are then examined in view of their interaction with intergroup issues such as ideologies, the formation of networks and language loss. While acknowledging the wide conceptual girth of EV, a central intergroup issue remains communication. Following through, issues pertaining to language acquisition are therefore scrutinized as they relate to EV, linguistic identification, and motivation. A parallel is drawn with Bourdeusian approaches, which orient the analysis toward the dynamics of power and investment. Specifically, attention is directed to ideological and identity processes underpinning the learner's involvement in the learning task. The paper concludes with a discussion of the relevance of the concept of global English as well as the necessity for a framework of contextual factors reaching beyond intrapsychic constructs.